2013
DOI: 10.2108/zsj.30.366
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Matrix Structure of Eggshells in the Testudines (Reptilia)

Abstract: The eggshells of 56 chelonians were examined by electron microscopy and X-ray diffractometry. They were classified into six types in terms of the matrix structure of their calcareous layer; type I was composed of a thin calcareous layer with minerals in an amorphous structure; type II with shell units composed of mammillary cores calcified with aragonite crystals; type III with shell units composed of mammillary cores, plus a single palisade layer also calcified with aragonite crystals, and with each shell uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 15 publications
1
42
0
2
Order By: Relevance
“…Turtles generally bury their eggs in moist sand or other type of wet soil (Witt and Caldwell 2004), so the implied fluvial environment seem to be ideal nesting site for turtles, making the absence of turtle eggshells even more puzzling. Since different extant turtles exhibit an astonishing diversity in the physical properties of their eggshells (Kusuda et al 2013), a possible explanation could be that the most abundant turtle known from the locality, the aquatic bothremydid Foxemys trabanti (Rabi et al 2011), laid soft-shelled eggs, as do numerous living turtles today. The potentially soft nature of turtle eggshells may account for their absence in the fossil record, since the depositional environment of Iharkút is clearly not favorable for preservation of soft tissues.…”
Section: Taphonomic and Paleoecological Implicationsmentioning
confidence: 99%
“…Turtles generally bury their eggs in moist sand or other type of wet soil (Witt and Caldwell 2004), so the implied fluvial environment seem to be ideal nesting site for turtles, making the absence of turtle eggshells even more puzzling. Since different extant turtles exhibit an astonishing diversity in the physical properties of their eggshells (Kusuda et al 2013), a possible explanation could be that the most abundant turtle known from the locality, the aquatic bothremydid Foxemys trabanti (Rabi et al 2011), laid soft-shelled eggs, as do numerous living turtles today. The potentially soft nature of turtle eggshells may account for their absence in the fossil record, since the depositional environment of Iharkút is clearly not favorable for preservation of soft tissues.…”
Section: Taphonomic and Paleoecological Implicationsmentioning
confidence: 99%
“…P. expansa has a flexible eggshell, and thickness recorded in the present study was 183 ± 1.405 μm. This parameter was also analyzed by Kusuda et al (2013), in several Testudines species that had flexible (146 to 268μm) and rigid eggshells (220 to 758μm). The results of the present study show that the thickness observed in P. expansa eggshells is in the same range of the values observed for other Testudines with flexible eggshells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chemical composition, ultrastructure, and porousness of reptile eggshells have been studied by many researchers. Packard, Packard, and Boardman (1982) analyzed eggshell structure and water relationships in reptile eggs ;Feder, Satel, & Gibbs (1982) analyzed the resistance of the eggshell membrane and the mineral layer in oxygen and water diffusion in flexible eggshells of Chelydra serpentine; Kitimasak et al (2003) studied the thickness, ultrastructure, and chemical composition of Chitra chitra eggshells; Osborne and Thompson (2005) described the chemical composition and structure of the eggshell in three lizard species; Areekijseree, Nuamsukon, Chuen-im, and Narkkong (2010) analyzed the ultrastructure and composition of Chelonia mydas eggshell elements; and Kusuda et al (2013) evaluated the structure of the calcareous layer, and classified Testudines eggshells.…”
Section: Introductionmentioning
confidence: 99%
“…First, the shell is made of aragonite crystals rather than calcite (Packard & DeMarco, ). Second, there is variation in the degree of calcification of the eggshell with some families laying hard, rigid‐shelled eggs whereas others lay pliable‐shelled eggs, although some of these are described as “soft‐shelled” (Ewert, ; Kusuda et al., ; Packard & DeMarco, ). Of the 13 families of the Testudinata, almost all species from six families lay rigid‐shelled eggs whereas the other families lay pliable‐shelled eggs but there seems to be no easily recognized evolutionary trend for eggshell structure within the Order (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…(2) And what are the functional consequences of this difference? It is possible that our distinction between shell types in the Testudinata (Kusada et al., ) is not biologically realistic and that there is a spectrum of eggshell calcification that has yet to be revealed by more widespread investigation of eggshell characteristics. However, there are elements of egg biology that do seem to be very different between the two groups.…”
Section: Introductionmentioning
confidence: 99%